2011
DOI: 10.1007/s12032-011-0058-y
|View full text |Cite
|
Sign up to set email alerts
|

High expression of S100A11 in pancreatic adenocarcinoma is an unfavorable prognostic marker

Abstract: S100A11 is a member of S100 protein family, and our previous study showed that S100A11 is one of the up-regulated proteins that have not been reported to be associated with pancreatic carcinoma. The purpose of this study was to investigate the relation between S100A11 expression and the clinicopathological variables and clinical outcome in patients with pancreatic adenocarcinoma. Immunohistochemistry analysis was performed for S100A11 in 78 pairs of specimens of human pancreatic adenocarcinoma tissues and adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 28 publications
3
38
0
Order By: Relevance
“…6). S100 proteins are therefore involved in the process of terminal differentiation of human epidermis and have been implicated in cancer as altered expression levels of several S100 proteins have been reported to correlate with tumor differentiation including ESCCs (7)(8)(9)(10)(11)(12)(13)(14). We have recently reported on the role of the S100 family member, S100A14, in driving esophageal carcinogenesis, showing that extracellular S100A14 affects esophageal cancer cell proliferation and apoptosis via interaction with RAGE, and intracellular S100A14 regulates cell invasion by MMP2 in a p53-dependent manner (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…6). S100 proteins are therefore involved in the process of terminal differentiation of human epidermis and have been implicated in cancer as altered expression levels of several S100 proteins have been reported to correlate with tumor differentiation including ESCCs (7)(8)(9)(10)(11)(12)(13)(14). We have recently reported on the role of the S100 family member, S100A14, in driving esophageal carcinogenesis, showing that extracellular S100A14 affects esophageal cancer cell proliferation and apoptosis via interaction with RAGE, and intracellular S100A14 regulates cell invasion by MMP2 in a p53-dependent manner (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is evidence suggesting that SCML2 may be involved in human tumors, including malignant pediatric brain tumors, acute myeloid leukemia and human hepatocellular carcinoma (30)(31)(32)(33)(34)(35)(36). The above knowledge about SCML2, together with previous findings on SCML2 expression in islet-cell carcinoma (12)(13)(14), inspired the investigation of a more explicit linkage between SCML2 and GEP-NETs, a tumor with an increasing incidence worldwide, in the present study. SCML2 expression was detected in GEP-NET tissues using immunohistochemical staining in the present study, and then SCML2 was compared with existing markers in terms of diagnostic value.…”
Section: Discussionmentioning
confidence: 72%
“…Afterwards, sections were further reacted with mouse IgGκ binding protein-HRP (sc-516102; 1:25; Santa Cruz Biotechnology, Inc.) for 30 min at room temperature. Slides were stained with diaminobenzidine and counterstained with hematoxylin as described previously (13,14). Sections were observed under a light microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, S100A11-RAGE interaction is correlated with the inflammation of chondrocytes (8). It has been reported that overexpression of S100A11 protein is associated with a number of cancers, including breast (9), colon (10), pancreatic (11), and papillary thyroid carcinoma (12). However, overexpression of S100A11 protein results in the contrary effect in ovarian (13) and bladder cancer (14).…”
mentioning
confidence: 99%